2021
DOI: 10.1088/1755-1315/890/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Fish hydrolysate supplemented diet improved feed efficiency and growth of coral trout (Plectropomus leopardus)

Abstract: Fish hydrolysate contains hydrolyzed protein which comprised of peptides and free amino acids that are easily digested and absorbed by fish. This study aimed to determine the effectiveness of fish hydrolysate in improving feed efficiency and growth of coral trout. Five experimental diets were formulated to contain 47% protein and 12% lipid with different sources and levels of fish hydrolysate. Diet-1 and diet-2 were added with crustacean hydrolysate at 2% and 4% levels, respectively. Whereas diet-3 and diet-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It has been reported that groupers have a low capability to utilize lipids as an energy source (Giri et al, 2021). Consequently, it is essential to formulate a diet that can improve feed efficiency and support the rapid growth of coral trout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that groupers have a low capability to utilize lipids as an energy source (Giri et al, 2021). Consequently, it is essential to formulate a diet that can improve feed efficiency and support the rapid growth of coral trout.…”
Section: Discussionmentioning
confidence: 99%
“…It has only been reported that juvenile coral trout require a dietary crude protein content of 50% for optimum growth (Xia et al, 2020). Compared with other grouper species, coral trout have a slower feeding process and relatively lower feed utilization (Giri et al, 2021). With this collective background, the present study aims to evaluate the effects of dietary bile acids on growth and feed utilization of coral trout.…”
Section: Introductionmentioning
confidence: 99%